Diagnostic and management approach to hyperglycemic hyperosmolar state in children with type 2 diabetes mellitus in limited settings - Syahrezki, Mohammad; Rochmah, Nur; Faizi, Mohammad; Hisbiyah, Yuni; Perwitasari, Rayi Kurnia (Edelweiss Applied Science and Technology, 2025)
Hyperglycemic Hyperosmolar State (HHS) is a triad characterized by severe hyperglycemia, significantly increased serum osmolality, and severe dehydration without marked ketoacidosis. It occurs in patients with both Type 1 and Type 2 Diabetes Mellitus. This case report discusses a 7-year and 9-month-old girl who presented to the hospital with shortness of breath and acidosis without evidence of ketonemia. The patient was moderately malnourished and had experienced increased urinary frequency over the past month. On examination, she was alert but had dry mucous membranes and visibly sunken eyes. Her laboratory results revealed a random blood glucose level of 1126 mg/dL, a blood pH of 6.97, and ketonuria of +1. Initially, the patient was misdiagnosed with diabetic ketoacidosis (DKA) at a previous hospital, leading to unresolved dehydration. Despite the absence of obesity or acanthosis nigricans, her normal C-peptide levels suggested Type 2 Diabetes Mellitus. Although DKA and HHS share some clinical features, they require distinct therapeutic approaches to reduce morbidity and mortality. The rarity of HHS in children and the lack of ketone testing in resource-limited settings pose significant challenges in its diagnosis.